2018
DOI: 10.3390/su10082748
|View full text |Cite
|
Sign up to set email alerts
|

A Cradle to Handover Life Cycle Assessment of External Walls: Choice of Materials and Prognosis of Elements

Abstract: This research focuses on a comparison of 20 external wall systems that are conventionally used in Spanish residential buildings, from a perspective based on the product and construction process stages of the life cycle assessment. The primary objective is to provide data that allow knowing the environmental behavior of walls built with materials and practices conventionally. This type of analysis will enable promoting the creation of regulations that encourage the use of combinations of materials that generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 79 publications
1
19
0
2
Order By: Relevance
“…PD and ID are the equipment operational time and idle This study attempts to search the environmentally friendly plan trade-off with project time and cost. The environmental assessment boundary follows the standard rules EN 15804:2012 + A1:2013 [46] and from a previous study [47]. It includes construction auxiliary materials from upstream extraction, processing, and production (A1-A3); major and auxiliary material off-site transportation (A4); and on-site equipment construction (A5).…”
Section: Performance Assessmentmentioning
confidence: 99%
“…PD and ID are the equipment operational time and idle This study attempts to search the environmentally friendly plan trade-off with project time and cost. The environmental assessment boundary follows the standard rules EN 15804:2012 + A1:2013 [46] and from a previous study [47]. It includes construction auxiliary materials from upstream extraction, processing, and production (A1-A3); major and auxiliary material off-site transportation (A4); and on-site equipment construction (A5).…”
Section: Performance Assessmentmentioning
confidence: 99%
“…The impact of Phases A1-A5 on the environment in the life cycle of a building wasstudied by the authors who concluded that this phase has aproportion of 8-20% [28][29][30][31][32][33][34][35][36]. The impact of thermal covers of a building on the environment in Phases A1-A5 was investigated by Gámez-García et al [37].…”
Section: Overview Of the Reference Papers Used For The Researchmentioning
confidence: 99%
“…Their studies [40] show that the current estimations of embodied energy are unclear and differ considerably, thus they conclude that guidelines are necessary, which would develop into globally accepted protocol for the calculation of embodied energy. The extensive study carried out by Gámez-García et al [37] on the impact of the applied materials in external walls of residential buildings in Spain shows the advantages and disadvantages of certain assemblies and negative impacts of gypsum boards. They claimed that 90% of the impact is generated during the process of production, whereas the process of construction solely contributes 1% of the impact [37].…”
Section: Overview Of the Reference Papers Used For The Researchmentioning
confidence: 99%
See 2 more Smart Citations